Contracting and Price Adjustment in Commodity Markets: Evidence from Copper and Oil - Hubbard, R. Glenn; Weiner, Robert J. (The Review of Economics and Statistics, 1989)
This paper analyzes price adjustment in markets where trade takes place through both spot-market and long-term-contract transactions. The authors develop a model illustrating the role of the resulting two-price system in describing price adjustment to transitory shocks; persistence effects of these shocks on prices depends on, inter alia, the fraction of trades carried out through contracts. The model is tested on price data from the world copper and crude oil markets. Econometric tests of the model provide support for the hypothesis that the increase in the importance of spot markets in copper and oil is associated with an increase in the speed of adjustment of spot prices to supply and demand disturbances. Copyright 1989 by MIT Press.